Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1002/mds.29298
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes and Parkinson's Disease: A Focused Review of Current Concepts

Abstract: Highly reproducible epidemiological evidence shows that type 2 diabetes (T2D) increases the risk and rate of progression of Parkinson's disease (PD), and crucially, the repurposing of certain antidiabetic medications for the treatment of PD has shown early promise in clinical trials, suggesting that the effects of T2D on PD pathogenesis may be modifiable. The high prevalence of T2D means that a significant proportion of patients with PD may benefit from personalized antidiabetic treatment approaches that also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 263 publications
0
5
0
Order By: Relevance
“…Diabetes and prediabetes increased the risk of PD by 27 and 4%, respectively, as compared to those without diabetes ( 17 ). Type 2 diabetes can enhance neurodegeneration through reduced brain insulin signaling, which can be more facilitated in patients with a lower BMI ( 18 ). Furthermore, an observational study showed that PD patients with diabetes were more severe in motor and non-motor symptoms and had a faster progression ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes and prediabetes increased the risk of PD by 27 and 4%, respectively, as compared to those without diabetes ( 17 ). Type 2 diabetes can enhance neurodegeneration through reduced brain insulin signaling, which can be more facilitated in patients with a lower BMI ( 18 ). Furthermore, an observational study showed that PD patients with diabetes were more severe in motor and non-motor symptoms and had a faster progression ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…DM constitutes a great global health challenge for around 460 million people worldwide [ 153 ]. According to preclinical assays, possible neuropathological mechanisms involved in these pathologies have been postulated [ 154 , 155 ]: (i) cerebrovascular disease; (ii) misfolding of proteins; (iii) chronic insulin resistance, which is associated with PGC-1α downregulation, mitochondrial complex I dysfunction, neuroinflammation, and impaired autophagy; (iv) amylin neuropathology. Amylin, a highly amyloidogenic pancreatic peptide, is increased in DM patients, can cross the BBB and accelerate α-syn [ 156 ] aggregation, Tau [ 157 ] phosphorylation, and Aβ [ 158 ] aggregates.…”
Section: Effects Of Ppars Agonists On Other Neurodegenerative Disordersmentioning
confidence: 99%
“…Because of FoxO1’s role in regulating brain metabolism, it may link metabolic dysfunction and neurodegenerative disease ( 185 ). For example, neurodegenerative diseases like Alzheimer’s disease (AD), Huntington’s disease (HD), and Parkinson’s disease (PD) are worsened by T2D ( 186 188 ), and FoxO1 expression is elevated in each of these conditions ( 189 193 ). Furthermore, increased FoxO1 has been shown to reduce pathological AD features such as tau hyperphosphorylation and amyloid beta (Aβ) plaques ( 190 , 194 196 ).…”
Section: Foxo1 and T2d – Brainmentioning
confidence: 99%